Development of an E-Commerce System from a Requirement of the OTOP Entrepreneurs in Nakhon Ratchasima - ชื่นธวัช รณชัย; รัตนสุพร เจษฎา; เนียนกระโทก ศรายุทธ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
This research aims to develop an E-commerce system from a requirement of the OTOP (One Tumbon One Product) distribution entrepreneurs in Nakhon Ratchasima. The sample set of this research is 15 OTOP entrepreneurs in Pakthongchai, Nakhon Ratchasima. In the development of E-commerce system, we develop a computer database as a relational database to store data that involve with OTOP products and develop a system as a website together with an Android mobile application. The design and development of an E-commerce system use the waterfall model integrate with the prototyping paradigm. When an E-commerce system was developed completely, we evaluated our E-commerce system by our sample set with an opinion questionnaire. From the results of evaluation, we found that the overview of evaluation was good. The issue of convenience to insert new product data has a minimum average score, it’s equal to 4.1. The issue of completeness to present a detail of data and the ability to alert order from customer have a maximum average score, it’s equal to 4.8. Therefore, we can conclude that an E-commerce system of this research meet with a requirement of the OTOP entrepreneurs.